Peran Guru dalam Pengembangan Pembelajaran - Muhammad Anwar HM (Prodi Manajemen Pendidikan Islam Institut Parahikma Indonesia, 2020)
The learning development has two characteristics; 1) the learning process totally involves a mental process of students – it does not only require students listen, take notes, but also requires students’ activities in the process of thinking. 2) The learning process establishes the atmosphere of dialogue and the debriefing process continuously directed to improve and enhance students' thinking skills. The ability to think can finally help to gain the knowledge that they construct by their own self. Education should be student-centered, reversal learning, learning by doing, developing social skills, cognitive, and emotional. It also develops curiosity, imagination, the nature of the godless, problem solving skill, students’ creativity, and deepening IMTAQ IPTEK.